2008
DOI: 10.22358/jafs/66601/2008
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of δ-aminolevulinic acid for livestock: blood characteristics and immune organ weight in broilers

Abstract: A study was conducted to evaluate the effects of δ-aminolevulinic acid (ALA) on blood characteristics and immune organ weight in broilers. One-day-old broiler chicks were randomly assigned to one of four dietary treatments with six replicates of 20 chickens each. Treatments were basal diet supplemented with 0, 5, 10 and 15 mg/kg ALA. The two-phase experimental diets were formulated to meet the NRC requirements for chicks and fed for 5 weeks. Growth performance was not affected by supplementation of ALA during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
(17 reference statements)
1
9
1
Order By: Relevance
“…However, in the current study, the ALA shown no effects on other blood characteristics (WBC, HCT and albumin) and weight of immune related organs. This is inconsistent with the result of Chen et al (2008b), who reported that the ALA added at least 5 mg kg − 1 increases WBC counts and relative immune organ weights (spleen and bursa of Fabricius) of broiler. The reason for this is not clear, and may be a high standard error associated with treatment with ALA alone.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…However, in the current study, the ALA shown no effects on other blood characteristics (WBC, HCT and albumin) and weight of immune related organs. This is inconsistent with the result of Chen et al (2008b), who reported that the ALA added at least 5 mg kg − 1 increases WBC counts and relative immune organ weights (spleen and bursa of Fabricius) of broiler. The reason for this is not clear, and may be a high standard error associated with treatment with ALA alone.…”
Section: Discussioncontrasting
confidence: 87%
“…Previous studies have shown that supplementation with ALA alone up to 50 mg kg − 1 diet had no effect on the growth performance of weanling pigs (Mateo et al, 2006;Chen et al, 2008a) and broilers (Chen et al, 2008b). Even though this study evaluated the effects of ALA combined with VC supplementation, the results further confirmed that ALA supplementation did not influence the growth performance of broilers.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In this review, we considered indices reflecting different levels of defense mechanisms of the immune system: white blood cell (WBC) count, differential count, and cell-mediated immunity, which involves soluble proteins and bioactive small molecules released by the activated cells, such as cytokines, as well as the membrane-bound receptors and cytoplasmic proteins that bind to molecular patterns expressed on the surfaces of invading pathogens. Hence, the immune response in the evaluated studies was addressed through an estimation of WBC count and lymphocyte count, as well as measurement of tumor necrosis factor (TNF)-α; insulin-like growth factor (IGF)-1; haptoglobin; plasma cortisol [ 8 ]; cluster of differentiation antigen positive cells 2, 4, and 8 (CD2+, CD4+, CD8+, respectively); the ratio of CD4+ to CD8+ cells; B-cells; major histocompatibility complex classes I and II [ 17 ]; rates of phagocytosis in blood mononuclear cells (MNC); mitogen concanavalin A and phytohemagglutinin-induced proliferation of blood MNC [ 16 , 22 ]; levels of cluster of differentiation 3 (CD3) mRNA in the spleen; plasma thiobarbituric acid reactive substances (TBARS); plasma ceruloplasmin concentration; expression of interferon-γ; inducible nitric oxide synthase (iNOS); interleukin (IL)-6 and TNF-like ligand 1A mRNA; levels of IL-2; toll-like receptor 2, 4, and 7 mRNA in the spleen during Escherichia coli lipopolysaccharide (LPS) stimulation; ceruloplasmin oxidase [ 16 ]; differential count of WBC [ 13 ]; immunoglobin G (IgG) [ 8 , 14 , 29 ]; and the weight of immune organs, such as spleen, bursa of Fabricius, liver, and the thymus [ 15 , 16 , 31 ]. Readers are encouraged to refer to Supplementary Table S1 for further details.…”
Section: Resultsmentioning
confidence: 99%